Enantioselective Vanadium Catalyzed Oxidative Coupling: Development and Mechanistic Insights - Kang, Houng (J Org Chem, 2018)
The evolution of a more reactive chiral vanadium catalyst for enantioselective oxidative coupling of phenols is reported ultimately resulting in a simple monomeric vanadium species combined with a Brønsted or Lewis acid additive. The resultant vanadium complex is found to effect the asymmetric oxidative ortho—ortho coupling of simple phenols and 2-hydroxycarbazoles with good to excellent levels of enantioselectivity. Experimental and quantum mechanical studies of the mechanism indicate that the additives aggregate the vanadium monomers. In addition, a singlet to triplet crossover is implicated prior to carbon-carbon bond formation. The two lowest energy diastereomeric transition states leading to the enantiomeric products differ substantially with the path to the minor enantiomer involving greater torsional strain between the two phenol moieties.